Polyamines and its analogue modulates amyloid fibrillation in lysozyme: A comparative investigation - Kabir, Ayesha; Jash, Chandrima; Payghan, Pavan V.; Ghoshal, Nanda; Kumar, Gopinatha Suresh (Biochimica et biophysica acta. General subjects, 2020)
Polyamines can induce protein aggregation that can be related to the physiology of the cellular function. Polyamines have been implicated in protein aggregation which may lead to neuropathic and non neuropathic amyloidosis. Change in the level of polyamine concentration has been associated with ageing and neurodegeneration such as Parkinson's disease, Alzheimer's disease. Lysozyme aggregation in the presence of polyamines leads to non neuropathic amyloidosis. Polyamine analogues can suppress or inhibit protein aggregation suggesting their efficacy against amyloidogenic protein aggregates. In this study we report the comparative interactions of lysozyme with the polyamine analogue, 1-naphthyl acetyl spermine in comparison with the biogenic polyamines through spectroscopy, calorimetry, imaging and docking techniques. The findings revealed that the affinity of binding varied as spermidine > 1-naphthyl acetyl spermine > spermine. The biogenic polyamines accelerated the rate of fibrillation significantly, whereas the analogue inhibited the rate of fibrillation to a considerable extent. The polyamines bind near the catalytic diad residues viz. Glu35 and Asp52, and in close proximity of Trp62 residue. However, the analogue showed dual nature of interaction where its alkyl amine region bind in same way as the biogenic polyamines bind to the catalytic site, while the naphthyl group makes hydrophobic contacts with Trp62 and Trp63, thereby suggesting its direct influence on fibrillation. This study, thus, potentiates, the development of a polyamine analogue that can perform as an effective inhibitor targeted towards aggregation of amyloidogenic proteins. [Display omitted] •Polyamines are implicated in protein aggregation leading to amyloidosis.•Comparative interaction of lysozyme with biogenic polyamines and analogue is reported.•Binding affinity was spermidine >1-naphthyl acetyl spermine > spermine.•Biogenic polyamines accelerated while the analogue inhibited rate of fibrillation.•Naphthyl group of analogue makes hydrophobic contacts with Trp62,Trp63 of Lysozyme.